2017
DOI: 10.1055/s-0043-100934
|View full text |Cite
|
Sign up to set email alerts
|

An Appraisal of Drug-Drug Interactions with Green Tea (Camellia sinensis)

Abstract: This review summarizes published in vitro, animal, and clinical studies investigating the effects of green tea (Camellia sinensis) extract and associated catechins on drug-metabolizing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 51 publications
(81 reference statements)
0
36
0
Order By: Relevance
“…Epigallocatechin gallate, a constituent of teas, has shown in vitro inhibition of Cytochrome P450 enzymes, including CYP1A2, CYP2C8, CYP2C9, and CYP3A4 (Albassam and Markowitz, 2017) and therefore has potential effects on the majority of conventional asthma drugs. Similarly, eucalyptus oil (Eucalyptus globulus Labill.)…”
Section: Labetalol Ugt1a1 Ugt2b7mentioning
confidence: 99%
“…Epigallocatechin gallate, a constituent of teas, has shown in vitro inhibition of Cytochrome P450 enzymes, including CYP1A2, CYP2C8, CYP2C9, and CYP3A4 (Albassam and Markowitz, 2017) and therefore has potential effects on the majority of conventional asthma drugs. Similarly, eucalyptus oil (Eucalyptus globulus Labill.)…”
Section: Labetalol Ugt1a1 Ugt2b7mentioning
confidence: 99%
“…In vitro studies showed that EGCG is a substrate for MRP1 and MRP2 but not for Pgp [ 35 ] and that ECG and EC may be substrates of MRP2 [ 36 ]. In addition, several studies suggest that green tea catechins inhibit Pgp as well as organic anion-transporting polypeptide (OATP)1B1, OATP1B3, organic cation transporter (OCT)1, OCT2, multidrug and toxin extrusion (MATE)1 and MATE2-K transporters [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids (such as epicatechin and catechin), furanocoumarins and alkaloids (such as caffeine) found in fruits, vegetables and herbs have been reported to modulate the activities of drug transporters such as Pglycoprotein and metabolizing enzymes [10,25]. For example, green tea extract and/or (−)-epigallocatechin-3gallate was demonstrated to reduce the bioavailability of quetiapine, sunitinib, clozapine, and nadolol by influencing the activities of drug-metabolizing enzymes and drug transporters [26]. Phytochemical evaluation of Cola nitida has indicated the presence of purine alkaloids such as caffeine and theobromine [6]; flavonoids such as epicatechin and catechin [7] in addition to saponins, cardenolides and tannins [4].…”
Section: Discussionmentioning
confidence: 99%